Optimizing Big Data for Human Resource Development in Madura’s Halal Tourism - Ummadinatus Sholehah; Farid Ardyansyah; Khoirun Nasik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Halal tourism has emerged as a strategic sector for enhancing regional competitiveness, particularly in Madura, where religious and cultural values form a strong foundation. Specific Background: Despite its potential, the development of halal destinations in Madura faces challenges related to the limited digital literacy and managerial capacity of local human resources. Knowledge Gap: Previous studies on the use of big data in tourism have mainly focused on digital business contexts, leaving a gap in understanding its role in strengthening human resources within halal tourism, especially in localized settings. Aims: This study aims to formulate strategies for improving the quality of halal tourism human resources through big data utilization using SWOT analysis. Results: Findings show that big data enhances the capacity of destination managers by enabling trend identification, targeted training, and data-driven decision-making. The analysis produced four strategies—aggressive, diversification, defensive, and survival—focusing on service innovation, capacity building, data security, and collaboration. Novelty: This research offers an integrative model linking digital technology and religious-cultural values for halal tourism management. Implications: The study contributes to academic discourse on digital-based destination management and provides practical insights for policymakers and stakeholders to strengthen Madura’s competitiveness in sustainable halal tourism. Highlights: Strengthens HR quality through big data-driven strategies. Integrates digital innovation with local religious values. Enhances Madura’s competitiveness in halal tourism development. Keywords: Big Data, Human Resources, Halal Tourism, SWOT Analysis